α-Well-Posedness for Mixed Quasi Variational-Like Inequality Problems - Jian-Wen Peng; Jing Tang (Abstract and Applied Analysis)
The concepts of α-well-posedness, α-well-posedness in the generalized sense, L-α-well-posedness and L-α-well-posedness in the generalized sense for mixed quasi variational-like inequality problems are investigated. We present some metric characterizations for these well-posednesses.